119 V/q single-photon emission computed tomography in non-thromboembolic pulmonary arterial hypertension. (5th June 2017) - Chan, Kenneth; Ioannidis, Stefanos; Coghlan, John G; Hall, Margaret; Schreiber, Benjamin E
Abstract : Background: Pulmonary arterial hypertension (PAH) is a rare cause of pulmonary hypertension (PH) with poor prognosis. Current guidelines recommend ventilation/perfusion (V/Q) scan in screening for thromboembolic cases of PH. We hypothesise that perfusion defects in non-thromboembolic PAH could also render abnormal V/Q scans, and sough to evaluate the incidence and clinical significance of abnormal V/Q SPECT in patients without thromboembolism. Methods: A total of 136 patients underwent V/Q SPECT (single-photon emission computed tomography) and right heart catheterization in our national PH service during 2013–2015 and were diagnosed with PH with mean pulmonary arterial pressure (mPAP) 25mmHg. V/Q mismatch suggesting thromboembolism was assessed according to European Association of Nuclear Medicine guideline. V/Q SPECT scans were further classified according to the pattern of perfusion defect, with focal defects typical for localised thromboembolism, and global perfusion defects. The results were compared with thromboembolism detected by computed tomography (CT) and invasive pulmonary angiography. All-cause mortality was recorded for a median follow-up of 1 year. Results: Abnormal V/Q SPECT with normal pulmonary angiography was found in 19 patients, and majority (78.9%) of these patients had PAH. After re-defining V/Q SPECT images according to the pattern of perfusion defects, compared to patients with focal perfusion defects or normal scans, those with global perfusion defects had higher mPAP (β²=7.55, 95% CI 2.85–12.3, p=0.002) and pulmonary vascular resistance (β²=195.4, 95% CI 59.3–331.5, p=0.006). Among patients with PAH, global perfusion defects were associated with higher all-cause mortality with hazard ratio 5.63 (95% CI 1.11–28.5) compared to those with local or no perfusion abnormalities. Conclusions: There is a high incidence of abnormal V/Q SPECT scans in non-thromboembolic PAH. An abnormal V/Q SPECT in the context of PAH is associated with a worse outcome.